The Secret Life of Secret Agents: Alan Bennett and John Schlesinger’s An Englishman Abroad (1983) and A Question of Attribution (1991) - Nicole Cloarec (Revue LISA)
Although biopics are still widely held in critical disdain, a number of new stimulating perspectives on the genre have recently emerged. One original approach consists in tackling the biopic as a form of adaptation and an example of intermedial rewriting, thus enabling to overreach the traditional fiction-versus-fact debate. This approach seems all the more appropriate when the main characters’ lives are notoriously elusive and shrouded in secrecy. Because their lives are wrapped in mystery, spies have long been figures of fascination and speculation, spawning some of the most long-lasting and profitable fictions in cinema. And yet, biopics about actual secret agents are scarce and scanty. How then to conceive of a film that deals with the lives of secret agents while accounting for the very secrecy that defines them? This is the challenge screenwriter Alan Bennett and director John Schlesinger have taken up in two films that form a diptych on two of the most notorious spies in British history, Guy Burgess in An Englishman Abroad (1983) and Anthony Blunt in A Question of Attribution (1991). While displaying a sustained concern for “national biography”, both films prove early examples of biopics conceived as self-reflexive and intermedial allegories. Rather than claiming to disclose the real ‘self’ of their biographees, the films choose to imaginatively engage with the deliberate entanglement of life and fiction while foregrounding their dramatic strategies of representations, leading to playful reflections on appearances, on the way they are coded and may be decoded.